PENGGUNAAN BAHAN ADITIF SEBAGAI BAHAN STABILISASI TANAH UNTUK LAPISAN PONDASI JALAN - Mauritius Ildo Rivendi Naikofi; Egidius Kalogo; Rikardus Sabon Doni; Engelbertha N.B. Seran (Program Studi Teknik Sipil Universitas Katolik Widya Mandira, 2022)
East Nusa Tenggara (NTT) is an archipelagic area with various characteristics of rock layers, most of which are dominated by limestone/coral. The condition of the dominance of coral rocks and the very minimal availability of sea transportation facilities greatly affect the rate of development in the area. Access to materials is quite difficult which results in material scarcity and the lack of equipment availability is a common condition in several areas in NTT. In the construction of road infrastructure, the problem of supplying aggregate according to specifications has its own difficulties in providing it. The absence of natural quarries for material supply is possible in the NTT region, especially on small islands, so there is a need for new breakthroughs to utilize existing materials at construction sites as foundation layers for road pavement so that the subgrade stabilization method as a foundation layer has a positive impact, especially minimize the gap in infrastructure development between one inhabited island and another in the NTT region